MAP3K1 Variant Causes Hyperactivation of Wnt4/β-Catenin/FOXL2 Signaling Contributing to 46,XY Disorders/Differences of Sex Development - Chen, Hong; Chen, Qingqing; Zhu, Yilin; Yuan, Ke; Li, Huizhu; Zhang, Bingtao; Jia, Zexiao; Zhou, Hui; Fan, Mingjie; Qiu, Yue; Zhuang, Qianqian; Lei, Zhaoying; et al. (Frontiers in Genetics, 2022)
Background: 46,XY disorders/differences of sex development (46,XY DSD) are congenital conditions that result from abnormal gonadal development (gonadal dysgenesis) or abnormalities in androgen synthesis or action. During early embryonic development, several genes are involved in regulating the initiation and maintenance of testicular or ovarian-specific pathways. Recent reports have shown that MAP3K1 genes mediate the development of the 46,XY DSD, which present as complete or partial gonadal dysgenesis. Previous functional studies have demonstrated that some MAP3K1 variants result in the gain of protein function. However, data on possible mechanisms of MAP3K1 genes in modulating protein functions remain scant. Methods: This study identified a Han Chinese family with the 46,XY DSD. To assess the history and clinical manifestations for the 46,XY DSD patients, the physical, operational, ultra-sonographical, pathological, and other examinations were performed for family members. Variant analysis was conducted using both trio whole-exome sequencing (trio WES) and Sanger sequencing. On the other hand, we generated transiently transfected testicular teratoma cells (NT2/D1) and ovary-derived granular cells (KGN), with mutant or wild-type MAP3K1 gene. We then performed functional assays such as determination of steady-state levels of gender related factors, protein interaction and luciferase assay system. Results: Two affected siblings were diagnosed with 46,XY DSD. Our analysis showed a missense c.556A > G/p.R186G variant in the MAP3K1 gene. Functional assays demonstrated that the MAP3K1R186G variant was associated with significantly decreased affinity to ubiquitin (Ub; 43–49%) and increased affinity to RhoA, which was 3.19 ± 0.18 fold, compared to MAP3K1. The MAP3K1R186G led to hyperphosphorylation of p38 and GSK3β, and promoted hyperactivation of the Wnt4/β-catenin signaling. In addition, there was increased recruitment of β-catenin into the nucleus, which enhanced the expression of pro-ovarian transcription factor FOXL2 gene, thus contributing to the 46,XY DSD. Conclusion: Our study identified a missense MAP3K1 variant associated with 46,XY DSD. We demonstrated that MAP3K1R186G variant enhances binding to the RhoA and improves its own stability, resulting in the activation of the Wnt4/β-catenin/FOXL2 pathway. Taken together, these findings provide novel insights into the molecular mechanisms of 46,XY DSD and promotes better clinical evaluation.